2017
DOI: 10.1177/1938640017706155
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Risk Factors for Complications in Elective Ankle and Hindfoot Reconstruction

Abstract: Level III: Retrospective comparative study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 60 publications
0
23
3
Order By: Relevance
“…By far, however, epidemiologic data on SSI following elective foot and ankle surgeries remain scarce. As far as we know, only very few studies focused on this subject and identified some risk factors, including alcohol use [ 10 ], preoperative narcotic use [ 10 ], advanced age [ 11 ], prolonged tourniquet time [ 11 ], tobacco use [ 11 ], complicated diabetes [ 4 ], perioperative antibiotics, and surgeon experience [ 12 ]. However, most of these risk factors were in controversy or inconclusive, which might be compromised by the small sample size or only inclusion of a specific population (diabetes mellitus, elderly, or foot and ankle trauma).…”
Section: Introductionmentioning
confidence: 99%
“…By far, however, epidemiologic data on SSI following elective foot and ankle surgeries remain scarce. As far as we know, only very few studies focused on this subject and identified some risk factors, including alcohol use [ 10 ], preoperative narcotic use [ 10 ], advanced age [ 11 ], prolonged tourniquet time [ 11 ], tobacco use [ 11 ], complicated diabetes [ 4 ], perioperative antibiotics, and surgeon experience [ 12 ]. However, most of these risk factors were in controversy or inconclusive, which might be compromised by the small sample size or only inclusion of a specific population (diabetes mellitus, elderly, or foot and ankle trauma).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the habit of smoking has been shown to increase the likelihood of surgical problems, as well as many postoperative complications, such as a higher incidence of infection and wound dehiscence after plastic surgery procedures 7 . Chronic exposure to cigarette smoke has been reported to have adverse effects on bone fracture repair and ligament healing that include heightened pain, longer hospitalization periods, and increased rate of hospital readmission 8 10 . Furthermore, smoking is considered a risk factor for non-healing and major amputation diagnosis in patients undergoing diabetic foot ulcer surgical treatment 11 , while a negative impact in number, size and overall healing of pressure injuries have also been reported 12 .…”
Section: Introductionmentioning
confidence: 99%
“…The effect of length of surgery and patient smoking on wound healing was previously evaluated in the literature. 6 , 7 , 10 , 23 , 24 , 27 , 29 Wiewiorski et al 30 evaluated 290 elective foot and ankle procedures and found an increase in postoperative wound-healing complications with higher tourniquet times (odds ratio = 7.02) and smoking (odds ratio = 48.77). Using a registry of 56,216 total knee arthroplasties, Namba et al 24 found a nearly 9% increased risk of infection per 15-minute increase in surgical time.…”
Section: Discussionmentioning
confidence: 99%